Opportunistic diseases among HIV-infected patients: a multicenter-nationwide Korean HIV/AIDS cohort study, 2006 to 2013 - Kim, Youn Jeong; Woo, Jun Hee; Kim, Min Ja; Park, Dae Won; Song, Joon-Young; Kim, Shin Woo; Choi, Jun Yong; Kim, June Myung; Han, Sang Hoon; Lee, Jin-Soo; Choi, Bo Youl; Lee, Joo Shil; et al. (The Korean journal of internal medicine, 2016)
The frequencies of opportunistic diseases (ODs) vary across countries based on genetic, environmental, and social differences. The Korean HIV/AIDS cohort study was initiated in 2006 to promote research on human immunodeficiency virus (HIV) infection in Korea, and to provide a logistical network to support multicenter projects on epidemiological, clinical, and laboratory aspects of HIV infection. This study evaluated the prevalence of ODs among HIV-infected patients in the era of highly active antiretroviral therapy, and the risk factors associated with ODs. The study enrolled 1,086 HIV-infected patients from 19 hospitals. This study examined the baseline data of the HIV/AIDS Korean cohort study at the time of enrollment from December 2006 to July 2013. Candidiasis was the most prevalent opportunistic infection (n = 176, 16.2%), followed by Mycobacterium tuberculosis infection (n = 120, 10.9%), Pneumocystis jirovecii pneumonia (n = 121, 11.0%), cytomegalovirus infection (n = 52, 4.7%), and herpes zoster (n = 44, 4.0%). The prevalence rates of Kaposi's sarcoma (n = 8, 0.7%) and toxoplasmosis (n = 4, 0.4%) were very low compared with other countries. The risk factors for ODs were a low CD4 T cell count at the time of HIV diagnosis (odds ratio [OR], 1.01; p < 0.01), current smoking (OR, 2.27; p = 0.01), current alcohol use (OR, 2.57; p = 0.04), and a history of tuberculosis (OR, 5.23; p < 0.01). Using recent Korean nationwide data, this study demonstrated that an important predictor of ODs was a low CD4 T cell count at the time of HIV diagnosis. Tuberculosis remains one of the most important ODs in HIV-infected patients in Korea.